Functionally graded adhesive joints by using thermally expandable particles. Issue 11 (19th September 2019) - Bonaldo, J.; Banea, M.D.; Carbas, R.J.C.; Da Silva, L.F.M.; De Barros, S.
ABSTRACT: The main objective of this work was to use thermally expandable particles (TEPs) in order to create a graded adhesive along the overlap by local mixing of the particles. Different amounts of TEPs were used along the overlap with two different adhesives used in automotive industry. Tensile and four-point bend tests were performed on single lap joints with hard steel adherends in order to investigate the behaviour of TEPs-modified graded joints. It was found that the strength of the joints under tension decrease with increasing TEPs content even for small amount of particles (i.e. 1 and 5%). However, a slight increase in strength was found for the graded joints compared to homogeneous joints modified with the same %wt TEPs. In the four-point bending test, the graded joints presented slightly higher strength, if compared with the homogeneous joints modified with the same wt% TEPs. 5%wt TEPs-modified joints presented the highest strength when submitted to bending loading. The experimental results are compared with a finite element model and generally a reasonably good agreement was found.